ACCOUNTING AND THE COURTS. - Briggs, L. L. (The Accounting Review, 1931)
Owing to the comparative youth of the accounting profession, court decisions affecting its members are few and scattering. However, the importance of these adjudications to the profession in inverse proportion to their number. An attempt is made in this article to state the significant parts of the American and English cases which have been decided during the past half century. Since accounting has attained the dignity of a profession, its members are subject to the same rules in their practice as are the members of other skilled professions. The damages claimed on account of the losses from the defalcations of the clerk and the insolvency of his surety are too remote to recovered, without showing the existence of special circumstances, known to defendants from which they ought to have known that much losses were likely to result from failure to disclose the true condition of affairs. Such losses are neither the natural nor the proximate consequences of the failure of defendants to make a proper audit.